Causes and prevention of occupational stress - Murtaza Mustafa; EM.Illzam; Rajesh Kumar Muniandy; MI.Hashmi; AM.Sharifa (International Organization of Scientific Research (IOSR), 2015)
Occupational stress can lead to one’s physical or mental state in response to workplace that pose a challenge to that employee. Causes of occupational stress include environments, organizational climate, and a conflict arises from the job demands of the employees. Physical symptoms of stress include fatigue, increased blood pressure, rapid heart rate,dizziness, headaches, jaw pain, back pain, inability to concentrate and confusion, immunosuppression and chronic pain. Psychologic disorders may lead to poor work performance, higher absenteeism, less work productivity even injury. Stressful working conditions can lead to behavioral, physical, and psychological strains. Adverse health effects include psychological disorders, cardiovascular disease, gastrointestinal disease, diabetes, hypertension, week immune system, increased risk of occupational injury and health service utilization. Interventions to eliminate or reduce the occupational stress should be both at organizational and individual levels. National Institute of Occupational Safety and Health (NIOSH) guidelines on organizational change to prevent occupational stress is useful.